Identifying the features of structural and phase transformations in processing the waste of metallurgical products doped with refractory elements - Volokh, V.; Kim, E.; Fesenko, T.; Petryshchev, A.; Artemev, S.; Tsymbal, B. M.; Makarenko, L.; Hedzyk, A.; Slabko, V.; Khmelovskyi, V.; Цимбал, Б. М. (ПП «ТЕХНОЛОГІЧНИЙ ЦЕНТР», 2020)
Phase composition and microstructure of the doping alloy obtained by regenerative smelting of technogenic wastes were studied. This is necessary to determine technological characteristics that increase the degree of extraction of doping elements during the processing of technogenic raw materials and subsequent use of the alloying material. It was determined that at a Si:C atomic ratio in the charge at a level of 0.05–0.19 (O:C atomic ratio is 1.25), a solid solution of carbon and doping elements in γ-Fe, Fe3Si, and Fe5Si3 was found in the alloy. At Si:C atomic ratio at a level of 0.05 in the alloy, a solid solution of carbon and alloying elements in γ-Fe was dominating with a weak manifestation of Fe3Si. When the value of Si:C atomic ratio was increased to 0.09, Fe5Si3 was found together with Fe3Si. A gradual increase in Si:C atomic ratio to 0.09, 0.12, and 0.19 led to a higher manifestation of Fe3Si and Fe5Si3. The microstructure of the alloy in the entire studied range of Si:C ratio values in the charge was characterized by the presence of several phases with different contents of doping elements. The content of elements in the studied areas (at. %) was 1.65–52.10 for Ni, 2.80–53.92 for Cr, 0.19–13.48 for Mo, 0.40–12.21 for W, 13.85–33.85 for Nb, 2.40–6.63 for Ti. An increase in Si:C atomic ratio in the charge from 0.05 to 0.19 caused an increase in silicon concentration in the studied areas of the microstructure (from 0.28 at. %) to 6.31 at. %. According to an analysis of the sample areas, carbon content was characterized by figures from 2.07 at. % to 14.23 at. %). Some of the investigated particles with a high content of W, Mo, Nb corresponded to complex carbide compounds with a high probability. Based on the study results, it can be pointed out that the most favorable Si C atomic ratio in the charge is 0.12 (with an O:C atomic ratio of 1.25). The resulting product had a relatively low content of silicon and carbon but was sufficient enough to provide the required reducing and deoxidizing strength of the alloy .
Keywords: oxide technogenic waste; scale of alloy steels; reduction smelting; X-ray phase studies